Change in oak to pine dominance in secondary forests may reduce shifting agriculture yields: experimental evidence from Chiapas, Mexico - Garcı́a-Barrios, Luis; González-Espinosa, Mario (Agriculture, ecosystems & environment, 2004)
In areas where fallow agriculture is practiced under increasing pressure on land, reduced soil fertility may derive not only from shorter fallow periods, but also from changes in floristic composition and structure in regenerating forest patches. The possible effects of these latter on soil fertility and subsequent crop yields has been largely neglected. The consequences of an observed shift from Quercus- (oak) to Pinus- (pine) dominated fallows on crop yields was investigated in the mountains of Chiapas, southern Mexico. Three successive crops, Zea mays L. var. praecox (popcorn), Triticum aestivum L. (common bread wheat), and a local landrace of Zea mays L. cv. “ olotón amarillo” were grown in 210 pots. Growth substrates obtained from forest microsites with similar climate, fallow period and soil type, but with different combinations of litter to mineral soil ratio (LR=grams of litter/grams of both mineral soil and litter) and pine litter dominance (PLD=grams of pine litter/grams of total litter), were used, with or without litter burning. Organic matter, total N, extractable phosphorus, pH, CEC, and soil C/N ratio were analyzed in 144 randomly chosen pots. Multiple regression analysis was used to assess the relative importance of LR, PLD, and burning or non-burning of litterfall on aboveground dry matter production and on soil variables. Increase in LR generally resulted in a positive effect on soil variables and crop yields; litter burning had a statistically significant effect ( P<0.01), but its favorable influence on yield was rather small. Pine dominance, as reflected in PLD, modified soil variables and reduced crop yields; its effects were relatively stronger when burning was prevented and when accumulated litter was low. Possible consequences of human-induced pine dominance on the soil resource base and on the dynamics of fallow agriculture are discussed.